Endoscopic Assisted Supraorbital Keyhole Approach or Endoscopic Endonasal Approach in Cases of Tuberculum Sellae Meningioma: Which Surgical Route Should Be Favored? - Linsler, Stefan; Fischer, Gerrit; Skliarenko, Volodymyr; Stadie, Axel; Oertel, Joachim (World Neurosurgery, 2017)
Objective Keyhole approaches are under investigation for skull base tumor surgery. They are expected to have a low complication rate with the same successful resection rate compared with endoscopic endonasal procedures. In this study, we compare our current series of tuberculum sellae meningiomas resected via an endoscopic endonasal or microsurgical supraorbital keyhole approach. Methods Between 2011 and 2016, 16 patients were treated using the supraorbital keyhole procedure and 6 patients received an endoscopic endonasal procedure. Both surgical techniques were analyzed and compared concerning complications, surgical radicality, endocrinologic, and ophthalmologic outcome and recurrences in patients' follow-up. Results The 2 different approaches yielded similar rates of gross total resection (endonasal 83% [5 of 6] vs. supraorbital 87% [14 of 16]), near total resection (17% [1 of 6] vs. 13% [2 of 16]), and visual recovery (endonasal 66% [2 of 3] vs. supraorbital 60% [3 of 5]). An extension lateral to the internal carotid artery was noted in 81% (13 of 16) of the supraorbital cases and in none of the endonasal cases. Tumor volume was 14.9 cm3 (±8.2 cm3) for supraorbital tumors versus 2.1 cm3 (±0.8 cm3) for the endonasal approach. Conclusions Both approaches provide minimally invasive surgical routes accessing meningiomas of the sellar region. The ideal approach should be tailored to the individual patient considering the tumor anatomy, lateral extension, and the experience of the surgeon with both surgical approaches. We suggest using the supraorbital approach for larger meningiomas of sellar region with far lateral extension or broad vascular encasement.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Endoscopic assisted surgery; Endoscopic endonasal approach; Meningioma; Skull base; Supraorbital keyhole approach; Tuberculum sellae